Performance evaluation for outdoor wireless scenarios based on IEEE 802.11b/g in the presence of co-channel interference - Roman Alcides Lara-Cueva; Michael Santiago Simba-Herrera (Bulletin of Electrical Engineering and Informatics, 2020)
Voice over Internet Protocol (VoIP) has evolved over the years, being a real-time service. VoIP has been coupled to different technologies, one of them is WiFi, which is one of the most used for wireless local area networks in domestic and commercial environments. In this paper, we evaluate the performance of wireless scenarios by considering VoIP traffic, based on WiFi technology in conformance with IEEE 802.11b/g in interfered outdoor scenarios, by considering an intrusive injection traffic technique, for codecs G711 (1 sample), G711 (2 samples), G723, G729 (2 samples), and G729 (3 samples), related to the main metrics associated to Quality of Service (QoS) parameters. Our results show the best performance was obtained with the codecs G723 and G729 (3 samples), obtaining up to 30 simultaneous voice connections with optimal values of delay, jitter and packet loss according to the recommendations given for VoIP by ITU-T, while the worst performance was obtained with the codec G711 (2 samples), obtaining only 5 simultaneous voice connections, reaching an efficiency loss of around 18% in a co-channel interference scenario.